Marawi a city of the living past - Eslao, Rufino O.
"Data for this chapter were taken from the Census Report of 1960, data furnished by three Maranao students of the University of the Philippines, and the personal observations of the writer when he was assigned at the Mindanao State University, Marawi City, from 1964-1966."
"Institutions of learning can provide leadership by maximizing their contributions to cultural diffusion and assimilation."
Keywords: Marawi City (Lanao del Sur) -- History